ANALISIS KELAYAKAN FINANSIAL USAHA PERKEBUNAN KARET PROGRAM EKS UPP TCSDP DI DESA BINA BARU KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Maya Utari; Yusmini Yusmini; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to analyze the financial feasibility of rubber plantation Ex UPP TCSDP at Bina Baru Village Kampar Kiri Tengah District Kampar Regency. Bina Baru Village obtain assist Ex UPP TCSDP from Plantantion Office of Riau for 258Ha rubbers plant, 1 Ha of rubber is given to one farmer. The instruments of this research are; analyzing the NPV, Net B/C and IRR and also sensitivity analysis. The used of data is primary data and secondary data. Primary data is price data were obtained from farmers and secondary data is physics data obtained from related agencies. The result shower that analyzing NPV is Rp.63.691.097,62, Net B/C is 2,62 and IRR is 25%. The farmer income in one year is Rp.2.547.643,90. Analyzing of sensitivity of the changes of the production around 25%which slope NPV is 53,83%. The changes of the input around 15% which slope NPV is 17,30%. The changes of the output around 41% which slope NPV is 88,28%. These proofed the rubber plan is still able to do if there is the changes of price and three aspects, because the NPV value still give positive value and Net B/C value >1 and also IRR bigger than discount factor 12%. Keyword: Rubber, Investment Criteria Analysis, Sensitivity Analysis.